Avaliação dos efeitos da temperatura e pressão na extração do eugenol das folhas de cravo (Syzygium aromaticum) utilizando CO2 supercrítico e cossolventes - Frohlich, Paula Cassiana (2019)
Aromatic plants are of great importance, due to their bioactive components and therapeutic properties that characterize them by the different activities, among them antioxidant, antifungal and antimicrobial. The clove (Syzygium aromaticum) is a tree which belongs to the family Myrtaceae whose essential oil has several applications, such in the food, cosmetic and pharmaceutical industries. Among the sundry extraction methods for essential oils, besides the conventional ones (hydrodistillation, Soxhlet), the supercritical extraction is notable for having a residue-free process and does not cause the thermal degradation of the extracts.In this context, the present study aims to evaluate the effect of the operational conditions on the extraction with supercritical CO2 of clove leaves on yield and eugenol content. The conditions used in the supercritical CO2 extraction were: temperatures of 40, 50 and 60 ºC and pressures of 150, 185 and 220 bar. The highest yield (1.08%) and higher eugenol content was obtained in the condition of 40 ºC and 220 bar. The main components identified in clove extract were eugenol (29.73%), chavicol (13.31%), n-pentacosane (11.66%), hexacosanal (11.37%) and vitamin E (9.30%). The extracts were evaluated for their antioxidant capacity by the DPPH and FRAP method and also the quantification of the phenolic compounds by the Folin-Ciocalteu method. The best results among the conditions were obtained at the lowest pressure and temperature, 150 bar and 40 ºC. The highest anti-microbial activity was observed for the extract obtained by supercritical CO2 (220 bar and 40 ºC) against Salmonella enterica subsp. Serovar Typhi (ATCC 06539). The Sovová model applied to represent kinetics of extractions satisfactorily represented the experimental data in all the conditions employed.